Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Let's solve the given exponential equation step by step:
The given equation is:
[tex]\[ e^{3x - 4} \cdot e^{-x} = 2e \][/tex]
First, we simplify the left-hand side. We know that when multiplying exponential expressions with the same base, we add the exponents:
[tex]\[ e^{3x - 4} \cdot e^{-x} = e^{(3x - 4) + (-x)} = e^{3x - 4 - x} = e^{2x - 4} \][/tex]
Now, our equation simplifies to:
[tex]\[ e^{2x - 4} = 2e \][/tex]
Next, we want to isolate the exponential expression. Since the right-hand side has an [tex]\(e\)[/tex], we can divide both sides by [tex]\(e\)[/tex]:
[tex]\[ e^{2x - 4} = 2e \][/tex]
[tex]\[ e^{2x - 4} / e = 2e / e \][/tex]
[tex]\[ e^{2x - 4 - 1} = 2 \][/tex]
[tex]\[ e^{2x - 5} = 2 \][/tex]
To solve for [tex]\(x\)[/tex], we take the natural logarithm (ln) of both sides of the equation. Applying the natural logarithm to both sides, we get:
[tex]\[ \ln(e^{2x - 5}) = \ln(2) \][/tex]
Using the property of logarithms that [tex]\(\ln(e^y) = y\)[/tex], we simplify the left-hand side:
[tex]\[ 2x - 5 = \ln(2) \][/tex]
Now, we solve for [tex]\(x\)[/tex] by isolating it on one side of the equation. First, add 5 to both sides:
[tex]\[ 2x = \ln(2) + 5 \][/tex]
Then, divide both sides by 2:
[tex]\[ x = \frac{\ln(2) + 5}{2} \][/tex]
We know that [tex]\(\ln(2) \approx 0.693\)[/tex]:
[tex]\[ x = \frac{0.693 + 5}{2} = \frac{5.693}{2} \approx 2.847 \][/tex]
Therefore, the solution to the equation, correct to the nearest thousandth, is:
[tex]\[ x \approx 2.847 \][/tex]
The given equation is:
[tex]\[ e^{3x - 4} \cdot e^{-x} = 2e \][/tex]
First, we simplify the left-hand side. We know that when multiplying exponential expressions with the same base, we add the exponents:
[tex]\[ e^{3x - 4} \cdot e^{-x} = e^{(3x - 4) + (-x)} = e^{3x - 4 - x} = e^{2x - 4} \][/tex]
Now, our equation simplifies to:
[tex]\[ e^{2x - 4} = 2e \][/tex]
Next, we want to isolate the exponential expression. Since the right-hand side has an [tex]\(e\)[/tex], we can divide both sides by [tex]\(e\)[/tex]:
[tex]\[ e^{2x - 4} = 2e \][/tex]
[tex]\[ e^{2x - 4} / e = 2e / e \][/tex]
[tex]\[ e^{2x - 4 - 1} = 2 \][/tex]
[tex]\[ e^{2x - 5} = 2 \][/tex]
To solve for [tex]\(x\)[/tex], we take the natural logarithm (ln) of both sides of the equation. Applying the natural logarithm to both sides, we get:
[tex]\[ \ln(e^{2x - 5}) = \ln(2) \][/tex]
Using the property of logarithms that [tex]\(\ln(e^y) = y\)[/tex], we simplify the left-hand side:
[tex]\[ 2x - 5 = \ln(2) \][/tex]
Now, we solve for [tex]\(x\)[/tex] by isolating it on one side of the equation. First, add 5 to both sides:
[tex]\[ 2x = \ln(2) + 5 \][/tex]
Then, divide both sides by 2:
[tex]\[ x = \frac{\ln(2) + 5}{2} \][/tex]
We know that [tex]\(\ln(2) \approx 0.693\)[/tex]:
[tex]\[ x = \frac{0.693 + 5}{2} = \frac{5.693}{2} \approx 2.847 \][/tex]
Therefore, the solution to the equation, correct to the nearest thousandth, is:
[tex]\[ x \approx 2.847 \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.